PENANGGULANGAN GAWAT DARURAT TERPADU DI DESA RIMBO RECAP - Bakara, Derison Marsinova; Khoirini, Fatimah; Mulyadi, Mulyadi; Almaini, Almaini (LPPM Universitas Al Muslim, 2024)
Farmers can experience emergencies in their work, which expose a higher risk of experiencing acute work-related injuries, certain chronic diseases, and diseases caused by pesticides. Long working hours, exposure to adverse weather conditions, and the use of equipment and machinery that pose serious hazards create a dangerous work environment. This community service activity aimed to form a standby farmer group to handle accidents and emergencies among farmer groups in Rimbo Recap Village, working area of ​​the District. Curup Selatan District. Rejang Lebong. The method for implementing community service activities used a learning and training approach, in the form of a lecture method to provide knowledge and demonstrations to improve skills in handling accidents and emergencies in farmer groups. Increased knowledge and skills of farmer groups in providing emergency assistance to farmers in the form of first aid for wounds, bandaging and splinting, first aid for pesticide poisoning, first aid for insect bites, and first aid for snake bites. This training can be used as a method to increase farmers' knowledge and skills in dealing with accidents and emergency cases that occur to farmers.